MANAJEMEN SUMBER DAYA MANUSIA (SDM) STRATEGIS STRATEGIC HUMAN RESOURCE MANAGEMENT (SHRM) DI LEMBAGA PENDIDIKAN - Muhammad Yunus Almator (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Strategic Human Resource Management (SHRM) using Dave Ulrich's model is a decisive factor in transforming educational institutions from administrative management toward competitive advantage. This study aims to analyze the implementation of Dave Ulrich's four HR roles—Strategic Partner, Change Agent, Administrative Expert, and Employee Champion—within educational institutions. The research method employed is a literature review with a descriptive-qualitative analysis of SHRM literature. The results indicate that the integration of the Strategic Partner and Change Agent roles enables educational institutions to align teacher competencies with future curricula and the dynamics of social change. Meanwhile, the Administrative Expert role ensures the efficiency of educational infrastructure, and the Employee Champion role enhances teacher well-being and engagement. The study concludes that the holistic adoption of Dave Ulrich's model allows educational institutions not only to survive competition but also to systematically improve the quality of learning through measurable and visionary talent management.